2001
DOI: 10.1111/j.1076-7460.2001.0639.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress Testing in the Elderly

Abstract: The ever-increasing number of older patients requiring diagnostic and prognostic assessment for coronary artery disease has necessitated accurate, noninvasive techniques applicable to this age group. Exercise testing, either alone or with radionuclide or echocardiographic imaging, remains a useful tool in elderly patients capable of performing vigorous treadmill or cycle exercise. Fortunately, for the large elderly subset incapable of such exercise, pharmacologic stress testing with dipyridamole, adenosine, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…211,294 In 419 CAD patients >65 years of age, one study revealed that severe ST-segment depression induced by cycle ergometry predicted triple-vessel disease. 295 Ischemic ST-segment depression predicted an increased risk of cardiac death in another study of older patients with stable CAD.…”
mentioning
confidence: 99%
“…211,294 In 419 CAD patients >65 years of age, one study revealed that severe ST-segment depression induced by cycle ergometry predicted triple-vessel disease. 295 Ischemic ST-segment depression predicted an increased risk of cardiac death in another study of older patients with stable CAD.…”
mentioning
confidence: 99%
“…Estudos indicam que doenças como hipertensão arterial, insuficiência cardíaca e arritmias são altamente prevalentes em idosos e têm um impacto substancial na homeostase, especialmente na regulação da pressão arterial e na composição do fluido corporal (Fleg et al, 2005).…”
Section: Prevalência E Impacto Dos Distúrbios Cardiovascularesunclassified
“…A prevalência de distúrbios cardiovasculares como hipertensão e insuficiência cardíaca em idosos tem implicações significativas na homeostase, especialmente na regulação da pressão arterial e equilíbrio hidroeletrolítico (Fleg et al, 2005).…”
Section: Impacto Dos Agravos Cardiovasculares Na Homeostaseunclassified
“…Exercise Treadmill Testing in the Elderly. Although exercise treadmill testing in elderly patients may pose special challenges due to decreased exercise tolerance, higher incidence of comorbidities, and mobility issues, treadmill testing retains a good safety profile in the elderly population 10,11 . Generally, lower workloads are achieved at the time of testing in elderly patients, and there is an increased incidence of comorbidities that may preclude exercise as a stressor.…”
mentioning
confidence: 99%